Automated assessment of absolute nailfold capillary number on videocapillaroscopic images: Proof of principle and validation in systemic sclerosis. (12th May 2018) - Cutolo, Maurizio; Trombetta, Amelia C.; Melsens, Karin; Pizzorni, Carmen; Sulli, Alberto; Ruaro, Barbara; Paolino, Sabrina; Deschepper, Ellen; Smith, Vanessa
Abstract: Background: Absolute nailfold capillary number should be a putative biomarker in selected rheumatic diseases but could be time‐consuming and not highly repeatable. Objective: To validate an automated software for absolute nailfold capillary number and density evaluation, on NVC images in SSc. Methods: An automated software to count nailfold capillary number (AUTOCAPI) had been constructed, through an exploratory image set. Subsequently, application rules have been created to define the ROI in NVC images, through a training images set. The software reliability was assessed through calculation of the ICC between automatic and manual counting, by four independent observers, on the same NVC images. Results: The following ICC's were obtained per observer, for the patients with SSc (40 images), the healthy (20 images), and the PRP subgroups (20 images), respectively: 0.94, 0.81, and 0.62 (observer 1); 0.94, 0.91, and 0.67 (observer 2); 0.88, 0.56, and 0.64 (observer 3); and 0.88, 0.85, and 0.85 (observer 4). Conclusions: The validation of an automated software for measuring absolute nailfold capillary number and density in SSc was achieved. The integration into the pre‐existing imaging software should make the assessment of the capillary number in NVC easier, quicker, and standardized.